A study of electron regeneration efficiency in fluorophore - N.F., Shaafi; S.B. Aziz, Aziz; M.F., Z. Kadird; Saifful Kamaluddin, Muzakir (Elsevier Ltd, 2020)
Archetypical excitonic solar cell consists of fluorophore (main light absorber), photoelectrode (electron transportation), and conducting polymer (electron regeneration). Fluorophore generates excited state electron upon absorption of light with sufficient energy. Electron in the highest occupied molecular orbitals (HOMO) would undergo an excitation to the lowest unoccupied molecular orbitals (LUMO) during the light absorption process. Therefore an electron vacancy in the HOMO of fluorophore is expected; need to be replenished for a continuous process of a photovoltaic mechanism. However the quantum of research on electron regeneration efficiency is still low due to limited computational facility. Two parameters are hypothesized to have significant impact on the electron regeneration process i.e., (i) conductivity (r), and (ii) redox potential (Eo) of the conducting polymer. This study aims to establish a correlation between the stated parameters with the photovoltaic conversion efficiency, g. Two conducting polymer were used in this work i.e., (i) alginate, and (ii) a mixture of 60 wt% of carboxymethyl cellulose (CMC) and 40 wt% of polyvinyl alcohol (PVA). The conductivity of the conducting polymer was calculated based on the measured bulk resistance using Electrical Impedance Spectrometer (EIS); showed that ralginate > rCMC/PVA. The redox potentials were calculated using quantum chemical calculations under the framework of density functional theory (DFT) at the level of b3lyp/lanl2dz. The lead sulphide thin film (fluorophore) was deposited using thermal evaporator on a pre-fabricated TiO2 layer on indium-doped tin oxide (ITO) conducting glass. The CMC/PVA-based cell yielded the highest g of 0.0015% under one-sun condition; showed higher g than that of the alginate conducting polymer. Therefore concluded that the conductivity would only determine the speed of the electrons during the regeneration. Nonetheless the efficiency of the regeneration process could be determined by the compatibility analysis of the conducting polymer and fluorophore. The compatibility analysis was carried out based on the energy level alignment between the Eo of the conducting polymer, and the HOMO energy level of the fluorophore. The calculated Eo of the conducting polymer used i.e., CMC/PVA is 3.144 eV, and alginate is 1.908 eV; incompatible to be paired with the fluorophore (PbS), which the HOMO, and LUMO energy levels are 5.100 eV, and 4.000 eV respectively. The low g of the CMC/PVA, and alginate-based cells however is speculated could also due to energy loss which is equivalent to 1.956 eV, and 3.912 eV energy offset respectively.